2008
DOI: 10.1073/pnas.0712147105
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified β-glucuronidase crosses blood–brain barrier and clears neuronal storage in murine mucopolysaccharidosis VII

Abstract: Enzyme replacement therapy has been used successfully in many lysosomal storage diseases. However, correction of brain storage has been limited by the inability of infused enzyme to cross the blood-brain barrier. The newborn mouse is an exception because recombinant enzyme is delivered to neonatal brain after mannose 6-phosphate receptor-mediated transcytosis. Access to this route is very limited after 2 weeks of age. Recently, several studies showed that multiple infusions of high doses of enzyme partially cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 31 publications
4
98
0
Order By: Relevance
“…This is in agreement with our previous studies16 showing that high enzyme doses are necessary to get sufficient amounts of enzyme into the CNS leading to a substantial reduction of brain storage when applied short term, suggesting a dose‐dependent uptake of the recombinant enzyme into the brain. Our studies are in agreement with other preclinical ERT studies in LSD animal models showing mostly beneficial effects of high‐dose injections of recombinant enzymes on primary lysosomal storage reduction and improvement of secondary pathological alterations such as neuroinflammation and behavioral deficits 29, 30, 31, 32, 33. Of note, in our preclinical study, the beneficial effect of ERT was most prominent for the 500 U/kg dosage but still significant at 125 U/kg for most of the parameters analyzed, suggesting that chronic treatment can at least to some extent compensate for lower enzyme activity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in agreement with our previous studies16 showing that high enzyme doses are necessary to get sufficient amounts of enzyme into the CNS leading to a substantial reduction of brain storage when applied short term, suggesting a dose‐dependent uptake of the recombinant enzyme into the brain. Our studies are in agreement with other preclinical ERT studies in LSD animal models showing mostly beneficial effects of high‐dose injections of recombinant enzymes on primary lysosomal storage reduction and improvement of secondary pathological alterations such as neuroinflammation and behavioral deficits 29, 30, 31, 32, 33. Of note, in our preclinical study, the beneficial effect of ERT was most prominent for the 500 U/kg dosage but still significant at 125 U/kg for most of the parameters analyzed, suggesting that chronic treatment can at least to some extent compensate for lower enzyme activity.…”
Section: Discussionsupporting
confidence: 91%
“…According to Sly and coworkers using recombinant GUS in preclinical ERT studies with MPSVII mice,24, 34 mannose‐6 phosphate receptors (MPRs) that are responsible for intracellular lysosomal targeting of most lysosomes enzymes and their cellular uptake35, 36 cannot account for the uptake of recombinant lysosomal enzymes into adult brain due to their restricted expression in brain endothelial cells within the perinatal period (2 weeks after birth). In adult animals which lack expression of endothelial MPRs, administration of recombinant enzymes bearing mannose 6‐phosphate (M6P) residues might even diminish their uptake into brain as demonstrated for GUS 24, 30, 34. Of note, recombinant rhLAMAN which, in comparison with other lysosomal enzymes, is highly efficient in clearance of brain primary substrate storage is only marginally phosphorylated, suggesting primarily M6P‐independent uptake 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sly and co-workers (17,27) have analyzed blood-to-brain transfer of the lysosomal enzyme ␤-glucuronidase in a mouse model of mucopolysaccharidosis type VII treated by ERT. The authors found that overexpression of MPR300 at the BBB increases cerebral ␤-glucuronidase levels and glycosaminoglycan clearance from brain cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Exposed carbohydrates of rhASA were inactivated by sodium metaperiodate treatment (17). One milligram of rhASA was incubated with a final concentration of 10 mM sodium metaperiodate in 100 mM NaCl/20 mM sodium phosphate (pH 6.0) for 30 min at 20°C.…”
Section: Chemical Modification Of Rhasamentioning
confidence: 99%